Qualitative and Quantitative Item Analysis of Essay Test Instruments in a Learning Planning and Microteaching Course - Ranu Iskandar; Putri Khoirin Nashiroh; Muhammad Khumaedi (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study aimed to conduct qualitative and quantitative analyses of essay test instruments used in the daily assessment of the Learning Planning and Microteaching course. This research employed a descriptive method with an item analysis approach. The subjects of this study were fifth-semester students of the Automotive Engineering Education Study Program, while the object of the study consisted of 15 essay items used in the daily assessment of the Learning Planning and Microteaching course. The study was conducted on September 25, 2025, involving 20 student respondents. Qualitative analysis of the test instrument was carried out by an expert to detect and correct weaknesses in the material, construction, and language aspects so that the instrument is valid in content and objective before being used. Quantitative analysis of test instruments is the process of testing the quality of test instrument items to determine item discrimination, Level of difficulty, and external validity reliability. The results showed that, based on the qualitative analysis, all items met the criteria for material, construction, and language aspects. However, the quantitative analysis, including difficulty index, discrimination index, validity, and reliability, indicated that several items required revision. Items 11 and 12 need revision because they showed weaknesses in validity, although their difficulty and discrimination indices were still acceptable. Meanwhile, items 2, 5, 8, 14, and 15 require more substantial revision or replacement because they have poor discrimination power. Overall, the essay test instrument can be considered moderately feasible, but it still requires improvement before being used as a strong formative assessment instrument.